Identity of the Teacher-Researcher in Collaborative Action Research: Concerns Reflected in a Research Journal - Darío Luis Banegas (Universidad Nacional de Colombia, 2012)
In this paper I report the insights of my personal research journal as part of a collaborative action research project I facilitated in a secondary school where I teach English as a foreign language. I kept a journal so as to offer the natural history of my research towards my doctoral degree. In this project I worked together with four participating teachers but I assumed a complex identity as I was a teacher-researcher i.e. doctoral researcher and a teacher. This entailed different roles and interests which generated opportunities and tensions. Qualitative analysis of my journal reveals complex concerns at different levels which signal the individual struggles of a teacher-researcher involved in collaboration.